Glow Up: Lifestyling dan Pembentukan Identitas Perempuan Muda Pengguna Produk Kecantikan Ala Korea - Elvi Bertha Debora (Jurnal Studi Pemuda, 2025)
The presence of Korean-style beauty products made in Indonesia serves as tangible evidence of the popularity of South Korea’s beauty industry, commonly referred to as K-Beauty, in Indonesia. These locally-produced Korean-inspired beauty products provide an alternative solution for young Indonesian women who are unable to access or afford original Korean beauty products, which are often categorized as high-end in the Indonesian market. This phenomenon, therefore, presents an intriguing subject for further study. The primary aim of this research is to examine how symbolic consumption practices, or lifestyling, are expressed through the use of Korean-style beauty products in Indonesia by young women, who serve as informants in this study. Additionally, the study explores the identity narratives that emerge from the use of Indonesian-made Korean-style beauty products. Using critical phenomenology and interviews conducted with four young women as users of these products, the findings reveal that the use of Indonesian-made Korean-style beauty products is primarily aimed at constructing an ideal self-identity.